Response of cold briquetted iron (CBI) to high temperatures treatment - Ibitoye S.A.; Adeleke A.A.; Tiamiyu A.O.; Popoola A.P.I.; Afonja A.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This investigation was carried out to assess the behaviours of Cold Briquetted Iron (CBI) when exposed to increasing temperature changes up to its complete melting. High-temperature behaviours and melting characteristics of CBI were studied. Ground as-received CBI briquette and those heated to temperatures ranging from 500°C to 1000°C were sieved to maximum of 30 microns diameter size and their room-temperature x-ray diffraction (XRD) measured. CBI was found to contain among others, α-iron, cementite and silica phases. Cementite was found to commence decomposition at 500°C - 600°C and completed by 700°C with conspicuous increase in the concentration of α-iron phase. Only α-iron and silica phases were sustained in CBI at temperatures above 700°C. In an inert atmosphere, it was discovered that CBI melted over a temperature range of 1527.3°C to 1536.96°C accompanied by an irrecoverable weight loss of 9.6 wt.% of the starting material. It was concluded that melting CBI would require charging along it appropriate fluxes to take care of the unreduced iron oxide and incorporation into facility for melting CBI an effective deslagging mechanism to remove unavoidable possible voluminous slag that would be formed.